Novel nanohydrogel based on itaconic acid grafted tragacanth gum for controlled release of ampicillin. (15th September 2018) - Pathania, Deepak; Verma, Chetna; Negi, Poonam; Tyagi, Inderjeet; Asif, Mohammad; Kumar, Nadavala Siva; Al-Ghurabi, Ebrahim H.; Agarwal, Shilpi; Gupta, Vinod Kumar
Graphical abstract: Highlights: Itaconic acid Nanohydrogel grafted tragacanth gum for controlled ampicillin release. Optimized pH (2.2) for maximum controlled ampicillin release using nanohydrogel. Pure tragacanth gum is inactive while synthesized nanohydrogel is active against bacteria. Itaconic acid grafted tragacanth gum is highly efficient nanohydrogel. Abstract: Nanohydrogel of tragacanth gum using microwave radiations is used for the controlled release of ampicillin. Tragacanth gum was grafted with itaconic acid, employing graft copolymerization in the presence of N, N 1 –methylene-bis-acrylamide (MBA) as cross linker, and potassium persulphate as initiator. The prepared nanohydrogel was characterized using FTIR, XRD, SEM, and TEM. Besides, the hydrogel was evaluated for in vitro drug release in distilled water and different pH values, and antimicrobial efficacy against E. Coli by well diffusion assay. In vitro drug release studies, at different pH values (2.2, 5.4 and 9.4), and distilled water, pH 2.2 was considered as the optimized pH for maximum drug release. Finally, through antimicrobial efficacy studies against E. Coli, it was observed that ampicillin loaded nanohydrogel, was more efficient in comparison to that of plain ampicillin drug.